The Anaerobically Induced sRNA PaiI Affects Denitrification in Pseudomonas aeruginosa PA14 - Tata, Muralidhar; Amman, Fabian; Pawar, Vinay; Wolfinger, Michael T.; Weiss, Siegfried; Häussler, Susanne; Bläsi, Udo (Frontiers in Microbiology, 2017)
Pseudomonas aeruginosa is an opportunistic pathogen that can thrive by anaerobic respiration in the lungs of cystic fibrosis patients using nitrate as terminal electron acceptor. Here, we report the identification and characterization of the small RNA PaiI in the Pseudomonas aeruginosa strain 14 (PA14). PaiI is anaerobically induced in the presence of nitrate and depends on the two-component system NarXL. Our studies revealed that PaiI is required for efficient denitrification affecting the conversion of nitrite to nitric oxide. In the absence of PaiI anaerobic growth was impaired on glucose, which can be reconciled with a decreased uptake of the carbon source under these conditions. The importance of PaiI for anaerobic growth is further underlined by the observation that a paiI deletion mutant was impaired in growth in murine tumors.